Gen Z, Gender variabel Dummy: Hedonic Shopping, Lifestyle, Dan Impulse Buying - Humairoh Humairoh; Mohammad Annas; M. Harry Mulya Zein (JMB : Jurnal Manajemen dan Bisnis, 2023)
The purpose of this examine became to analyze hedonic shopping and shopping lifestyle on impulse buying in Gen Z and gender as a moderating variable on impulse buying. This observe uses a causal associative method. The population in this observe is all generation Z in Tangerang city who shop at e-commerce. This examine took a sample of 100 respondents. Respondents from 13 districts in the Tangerang city location were taken through simple random sampling method. data collection the use of the online questionnaire application on the Google form was evaluated using a 5-point Likert scale, starting from 1=strongly disagree to five=strongly agree. statistics were analyzed using multiple linear regression operated through the SPSS version 26 software. primarily based at the results of the evaluation based totally on the purpose of producing hedonic shopping, it has a positive and significant effect on impulse buying in generation Z, shopping lifestyle has a positive and significant impact on impulse buying. Hedonic shopping and buying lifestyle have a positive and significant effect on impulse buying. Gender is a moderating variable between hedonic shopping and shopping lifestyle variables toward impulse buying. based totally at the effects of the regression equation with the gender dummy, women's impulsive buying is 0.18 factors higher than men's.Keywords: Hedonic Shopping, Shopping Lifestyle, Impulse Buying, Gender, Gen Z.